Micelle Formation in Myristyltrimethyl Ammonium Bromide at Different Solvent Composition of Ethanol Water Mixed Solvent Media - Shrestha, Prem Kumar; Mitruka, Jaya Narayan; Chapagain, Subash Kumar (Journal of Nepal Chemical Society, 2017)
Available with fulltext.